O Ensino Da Língua Portuguesa Escrita Para A Criança Surda Em Uma Perspectiva Bilíngue - Matos, Daniela Schlic [UNIFESP] (2017)
In this research, based on Vygotsky's socio-historical-cultural theory (1922-1934), we seek to better understand and reflect upon Portuguese teaching practices for deaf children, in a bilingual perspective, in which Libras – Brazilian Sign Language - is considered the first language and Portuguese, the second, seeking to know the Portuguese language teaching strategies and the role(s) that Libras plays within them. The research follows the Critical-Collaborative Methodology Paradigm (MAGALHÃES, 2007), and was carried out in a class of 1st grader in a Bilingual Education School for the Deaf (EMEBS), in the city of São Paulo. In addition to the socio-historical-cultural theory, the investigation is theoretically based on the current legal documents that support the bilingual education proposal for the deaf and provide guidelines for the teaching of Portuguese for the targeted audience, and authors such as Quadros (1997), Fernandes (2003) and Pereira (2009), who recognize Libras as the first language of the deaf in Brazil, and discuss the teaching of Portuguese as a second language to deaf people. Furthermore, in terms of teacher education, the thesis is based on Libâneo (2013), Gatti (2013), Mizukami (2013) and Nóvoa (2013). The data produced and analyzed indicate that, although the official proposal of Portuguese teaching for the deaf follows the guidelines that the language should be taught from a discursive perspective, looking at the text as a discursive unit, Portuguese teaching practices still persist with priority being given to the teaching of isolated words: naming objects, people and events, which hinder the development of reading fluency.